(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The effect of post-harvest treatment of maleic hydrazide (MH)with and without waxing on the quality and shelf-life of ‘Kitchner’ and‘Abu-Samaka’ mango fruits at 18 ±1°C and 85% - 90% relative humiditywas studied. Maleic hydrazide and wax treatments delayed fruit ripening,reduced losses, maintained quality and extended shelf-life of mangofruits. MH at 500 and 1000 ppm significantly delayed fruit ripening bytwo and four days in both mango cultivars, respectively, compared withthe untreated fruits. The higher the concentration of MH, the more delayin fruit ripening. Waxing in addition to MH treatment resulted in ripeningdelay of six days in fruit ripening than treatment with MH alone. Theeffect of MH and waxing treatments in delaying mango fruit ripening,was indicated in retarded respiratory climacteric, reduced water loss,delayed peel colour development, fruit softening and total soluble solidsaccumulation and retained ascorbic acid content.